THE RELATIONSHIP BETWEEN BILINGUALISM AND EMOTION PERCEIVED BY VIETNAMESE COLLEGE STUDENTS - Thai, Tram Thi Ngoc; Nguyen, Ngoc Le Bao (Universitas Negeri Malang, 2021)
Studies of the correlation between language and emotion have demonstrated the existence of a causal relationship between switching languages and feeling different in bi-/ multilinguals. Adopting the mixed-method approach, the current research aims to extend this line of enquiry to Vietnam – a monolingual country – by investigating 160 Vietnamese-English speaking students at International University (IU) (VNU-HCMC). They were required to complete a questionnaire based on the Bilingualism and Emotion Questionnaire (Dewaele & Pavlenko, 2001–2003). It includes closed questions concerning shifts on five scales of feelings and an open explanatory question on the difference perceived. The scales, chosen with reference to the research of Dewaele and Nakano (2012), consist of feeling logical, serious, emotional, fake, and different. Statistical analyses revealed a regular shift on most scales, with most participants feeling more logical, more serious, more fake, more different, and less emotional when using the L2. Simple linear regression revealed that the variation in certain feelings scales was mostly predicted by self-perceived proficiency in the L2